Konsep dan Penerapan Teori Belajar Populer di kelas - Mutiara Vidazeya; Neviyarni S; Herman Nirwana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This article discusses four relevant learning models in the context of contemporary education: Project-Based Learning (PBL), Quantum Learning, Self-Directed Learning (SDL), and Contextual Learning. These four models have different yet complementary approaches to improving the quality of learning. PBL emphasizes project-based learning that engages students in solving real-world problems, while Quantum Learning focuses on developing students' potential through engaging and holistic learning experiences. SDL allows students the freedom to manage their own learning, while Contextual Learning connects subject matter to real-life situations to make learning more relevant. Each model has advantages and challenges that need to be considered in its implementation in the classroom. It is hoped that by implementing these models, the learning process will become more effective and enjoyable, and can prepare students to face future challenges.